The Value of Information in Technology Adoption - Asad Islam; Philip Ushchev; Yves Zenou; Xin Zhang (Research Institute of Industrial Economics (IFN), 2020)
We develop a theoretical model in which technology adoption decisions are based on the information received from others about the quality of a new technology and on their risk attitudes. We test the predictions of this model using a randomized field experiment in Bangladesh. We show that the share of treated farmers who receive better training in System of Rice Intensification (SRI) technology have a high positive impact on the adoption rate of untreated farmers. We also find that untreated farmers who are more risk-averse tend to adopt the technology less and are less influenced by their treated peers. Our results thus indicate that spillover effects are important in technology adoption and that information transmission about the quality of the technology matters
Keywords: O13; Z13; 330; Technology adoption; Peers; Risk attitude; RCT; Bangladesh